ANALISIS YURIDIS TERHADAP LEGALITAS SUATU SURAT KEPUTUSAN PEMBERHENTIAN PEGAWAI NEGERI SIPIL OLEH BUPATI KABUPATEN MALUKU TENGGARA BARAT - Laritmas, Selfianus (EDUTECH CONSULTANT, 2019)
The State Civil Apparatus hereinafter abbreviated (ASN) is the profession of Civil Servants who are subsequently written (PNS), Provisions regarding the dismissal of Civil Servants are regulated in Law Number 5 Year 2014 concerning State Civil Apparatus, then Law No. 5/2014 is written. Matters that are reasons for dismissal of civil servants in article 87 paragraph 1 (one), paragraph 2 (two) and paragraph 4 (four) are civil servants dismissed with respect because: a. Dies; b. at own request; c. reaching retirement age; d. organizational downsizing or government policies that result in early retirement or e. incompetent physically and / spiritually so that they cannot carry out their duties and obligations, paragraph 2 (two) civil servants can be dismissed because they are sentenced to imprisonment based on court paragraph 4 (four) commit fraud against Pancasila and the 1945 Constitution of the Republic of Indonesia, b. sentenced to imprisonment or confinement based on a court decision that has permanent legal force because of committing a crime of occupational crime or a criminal offense related to position and / or general criminal offenses.